Fuzzy logic: a means of handling uncertainties in expert systems (2005)
This paper discusses on historical perspective of the evolution of fuzzy logic from the Boolean or crisp logic as well as some noteworthy objections to its use. Some fundamental notions on fuzzy set and fuzzy logic as well as the application areas are considered. The use of fuzzy logic in application involving imprecision and uncertainty is also discussed. An introductory account on expert systems and the basic components necessary for its development especially the knowledge base is presented. The main subject of this paper which is the applicability of fuzzy logic in handling of uncertainty in expert system is illustrated with two examples. Though the two illustrations used involve the use of expert systems in fault diagnosis in the field of electrical and electronic engineering which is the area of specialization of the author, they could easily be adapted to fault diagnosis in other areas.